2013
DOI: 10.1007/s10532-013-9675-9
|View full text |Cite
|
Sign up to set email alerts
|

3-Nitrotoluene dioxygenase from Diaphorobacter sp. strains: cloning, sequencing and evolutionary studies

Abstract: The first step in the degradation of 3-nitrotoluene by Diaphorobacter sp. strain DS2 is the dihydroxylation of the benzene ring with the concomitant removal of nitro group. This is catalyzed by a dioxygenase enzyme system. We report here the cloning and sequencing of the complete dioxygenase gene with its putative regulatory sequence from the genomic DNA of Diaphorobacter sp. strains DS1, DS2 and DS3. Analysis of the 5 kb DNA stretch that was cloned, revealed five complete open reading frames (ORFs) encoding f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…strain DNT (12), and 3-nitrotolueneutilizing Diaphorobacter species strains (11). Nevertheless, it is not known whether a functional internal promoter containing the 18-bp direct repeat is present for the enhanced expression of catabolism enzymes in these strains, in addition to the expression directed by Nag-like regulators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…strain DNT (12), and 3-nitrotolueneutilizing Diaphorobacter species strains (11). Nevertheless, it is not known whether a functional internal promoter containing the 18-bp direct repeat is present for the enhanced expression of catabolism enzymes in these strains, in addition to the expression directed by Nag-like regulators.…”
Section: Discussionmentioning
confidence: 99%
“…strain U2, the catabolism of naphthalene is initiated by naphthalene dioxygenase NagAaAbAcAd (7). This Nag dioxygenase is thought to be the progenitor of nitroarene dioxygenases (collectively called Nag-like dioxygenase) described so far (8), including nitrobenzene dioxygenase (9), 2-nitrotoluene dioxygenase (10), 3-nitrotoluene dioxygenase (11), and 2,4-dinitrotoluene dioxygenase (12,13). The synthetic nitro-and chloroaromatic compound, 2-chloronitrobenzene (2CNB), has been in the environment only for a short period of time.…”
Section: Importancementioning
confidence: 99%
“…Interestingly, 3NTDO from Diaphorobacter sp. strain DS2 has an isoleucine at position 204 and a glycine at position 405 (50). Modeling based on the structure of NBDO indicated that 3NTDO from Diaphorobacter has a larger active site than does NBDO (50).…”
Section: Discussionmentioning
confidence: 99%
“…strain DS2 has an isoleucine at position 204 and a glycine at position 405 (50). Modeling based on the structure of NBDO indicated that 3NTDO from Diaphorobacter has a larger active site than does NBDO (50). It is possible that the glycine at position 405 plays a role in determining the larger size of the active site.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas sp., by producing catechol 2, 3-dioxygenase (C23O) can utilize and decomposition polycyclic aromatic hydrocarbons (PAHs). C23O is a nonheme iron dioxygenase and a key enzyme in the biodegradation of PAH compounds that is released into the environment by a large number of an industrial process by catalyzing the conversion of catechol to 2-hydroxymuconic semialdehyde (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%